Answer:
None of them
[tex]x\geq -9[/tex]
Step-by-step explanation:
[tex]27[/tex] minus a number [tex]x[/tex] is not more than [tex]36[/tex] translates algebraically to
[tex]27-x\leq 36[/tex]
(Not more than [tex]36[/tex] means either [tex]36[/tex] or less than [tex]36[/tex] that's why we have used equal or less than inequality)
[tex]27-x\leq 36[/tex]
Subtract 27 from both sides
[tex]-27+27-x\leq 36-27[/tex]
[tex]-x\leq 9[/tex]
Multiply both sides by -1
Multiplying by -1 will reverse the inequity
[tex]x\geq -9[/tex]
Hence values of [tex]x[/tex] equal or greater than [tex]-9[/tex] will satisfy the inequality
Verification:
Lets take [tex]x=-4[/tex]
[tex]27-x\leq 36[/tex]
[tex]27-(-4)\leq 36[/tex]
[tex]27+4\leq 36[/tex]
[tex]31\leq 36[/tex] (satisfied)
Lets take [tex]x=2[/tex]
[tex]27-x\leq 36[/tex]
[tex]27-(2)\leq 36[/tex]
[tex]25\leq 36[/tex] (satisfied)